Patient safety culture in Palestine: university hospital nurses' perspectives - Loai M. Zabin; Rasha S. Abu Zaitoun; Abdullah A. Abdullah (BMC, 2022)
Abstract Background Understanding the perspectives of healthcare workers toward patient safety-related activities is critical in maintaining a healthy safety climate. The objectives of this research are 1) to examine the perception of Patient Safety Culture (PSC) at a university hospital in Palestine, and to highlight areas in need of improvement, and 2) to assess the relationship between the outcome dimensions (frequency of events reported, and overall perceptions of safety) and the other dimensions of PSC, and 3) to determine the relationship among selected demographic variables (gender, age, hospital tenure, work tenure, profession tenure, and hours worked per week) and nurses' perceptions of PSC. Methods A cross-sectional study design was used with a convenience sample of 107 nurses. Nurses were asked by email to complete the Arabic version of the Hospital Survey of Patients' Safety Culture (HSOPSC) using the SurveyMonkey® online account form within two weeks. The survey data were analyzed using descriptive and inferential statistics. Univariate and multiple regression were used to examine the relationships. Results The dimensions of patient safety with the highest positive response were organizational learning and continuous improvement (87%) and teamwork within units (86%). The dimension with the lowest positive score was the nonpunitive response to error (22%). Multiple regression revealed that the dimension of communication openness was a predictor of the overall perceptions of safety (β = 0.257, p = 0.019). In addition, the dimension of feedback and communication about error was a predictor of the frequency of the reported events (β = 0.334, p = 0.005). Furthermore, age was found to be a predictor of PSC (p < 0.05). Conclusions This study provides a general assessment of perceived safety among nurses in a hospital. However, we found that nurses negatively perceive a nonpunitive response to error. Therefore, strenuous efforts are required by hospital management to improve the culture of incident reporting.